Percutaneous Dilatational Tracheostomy - An Update - Najmuddin, Asif; Surani, Salim (Current Respiratory Medicine Reviews, 2014)
Percutaneous dilatational tracheostomy (PDT) is one of the most common procedures performed universally in patients admitted to medical and surgical intensive care units. Initially popularized in the 1980s, it can be performed by various techniques including Ciaglia’s blue Rhino, Griggs guide wire dilating forceps, Blue Dolphin, or the Perc Twist method. Bronchoscopy and ultrasound guidance have made these procedures much quicker and safer. Its main advantages over its centuries old counterpart, surgical tracheostomy (ST), include shorter procedure times, less perioperative bleeding, and a decreased risk of peristomal infection. PDT also appears to be more cost effective by preventing delays due to operating room scheduling issues and complications in transporting critically ill patients to the operating room for ST. Some patients, including those who are morbidly obese, those with prior tracheostomies, or patients with severe head and neck surgeries still remain good candidates for ST in general. Moreover, in experienced hands, PDT can also be performed. There are many physiological advantages of tracheostomy over the endotracheal tube such as reduction of airway resistance and anatomic dead space. Also, studies have shown decreased incidences of pneumonia, shorter inpatient stay length and reduced mortality with early tracheostomy. Nevertheless, the dilemma of appropriate timing to perform tracheostomy in the course of mechanical ventilation remains unanswered.
Keywords: percutaneous dilatational tracheostomy